2020
DOI: 10.3390/nu12082242
|View full text |Cite
|
Sign up to set email alerts
|

Energy Density of New Food Products Targeted to Children

Abstract: High dietary energy density (ED) is linked to childhood obesity and poor diet quality. The Australian Health Star Rating (HSR) system aims to assist consumers in making healthful food choices. This cross-sectional study used 2014–2018 data from the Mintel Global New Products Database to describe the ED of new food products targeted to children (5–12 years) released after the introduction of HSR and examine relationships between ED and HSR. Products were categorised by ED (low < 630 kJ/100 g, medium 630–950 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Low energy density can be a problem because the small stomachs of babies and young children limit them to relatively small amounts of consumption at mealtimes. Conversely, some products in the sweet snacks category that are suitable for children above 6 months have a high energy density, thus enhancing the risk of excessive energy intake and unfavourable gain in body mass [40].…”
Section: Discussionmentioning
confidence: 99%
“…Low energy density can be a problem because the small stomachs of babies and young children limit them to relatively small amounts of consumption at mealtimes. Conversely, some products in the sweet snacks category that are suitable for children above 6 months have a high energy density, thus enhancing the risk of excessive energy intake and unfavourable gain in body mass [40].…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of berry powder increased the content of fibre in the pastes, whilst decreasing starch content. The decrease in starch content could be explained by the dilution factor of berry powder, which contained lower starch content (Azzopardi et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Data collection systems varied within studies. The majority of articles collected information directly from packages (n = 18) [20,[27][28][29][30][31]34,35,37,41,42,45,50,51,54,55,57,61], three studies used self-reported information from foundations or manufacturers [49,53,56], two gathered information through a review of the literature [33,38], and one study had no information on data collection [40].…”
Section: Labeling Uptakementioning
confidence: 99%
“…Overall, food retailers were the most common users of voluntary labels, labeling products of their own brands [20,31,35,45,49,55,57]. In contrast, manufacturers' brands had lower [31,50] and more selective uptakes [49,54], leaning towards displaying labels on products with healthier scores [27][28][29]35,37,42,50,51,55,57].…”
Section: Labeling Uptakementioning
confidence: 99%